2008
DOI: 10.1002/term.117
|View full text |Cite
|
Sign up to set email alerts
|

Titanium foam-bioactive nanofiber hybrids for bone regeneration

Abstract: We have reported previously a method to introduce bioactive nanofiber networks through selfassembly into the pores of titanium alloy foams for bone repair. In this study we evaluate the in vitro colonization by mouse pre-osteoblastic cells of these metal-peptide amphiphile hybrids containing phosphoserine residues and the RGDS epitope. The aim was to determine the effect of varying the RGDS epitope concentration within a given range, and confirm the ability for cells to infiltrate and survive within the nanofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…As a general rule, nanomatrices provide more surface area for cell and growth factor attachment and are more biocompatible scaffolds for bone growth relative to conventional carriers. [37][38][39] Researchers have also demonstrated the ability of nanometric biomaterial surfaces to successfully modulate the adhesion and differentiation of osteoprogenitor cells down the osteoblastic pathway. 40 Finally, the use of nanoscale implants has been shown to reduce local fibroblast activity, which may prevent incorporation into host bone and implant failure.…”
Section: Discussionmentioning
confidence: 99%
“…As a general rule, nanomatrices provide more surface area for cell and growth factor attachment and are more biocompatible scaffolds for bone growth relative to conventional carriers. [37][38][39] Researchers have also demonstrated the ability of nanometric biomaterial surfaces to successfully modulate the adhesion and differentiation of osteoprogenitor cells down the osteoblastic pathway. 40 Finally, the use of nanoscale implants has been shown to reduce local fibroblast activity, which may prevent incorporation into host bone and implant failure.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo and in vitro studies have shown that certain PA molecules, bearing bioactive epitopes promote regeneration of spinal cord axons, angiogenesis, bone regeneration, cartilage repair, and selective differentiation of neural progenitor cells into neurons. (Sargeant, 2008;Silva, 2004) Previously, PAs were used to coat PGA microfiber scaffold for the improved attachment of smooth muscle cells. (Harrington, 2006;Behanna, 2005) This PGA scaffold was submerged in a suspension of smooth muscle cells in media and modified with PA gel mixed with growth factors as a top layer for the entrapment of cells.…”
Section: Bioactive Peptides and Peptide Amphiphiles For Regeneration mentioning
confidence: 99%
“…[133] With 15% molar of RGDS epitope used in the nanofiber networks, all samples demonstrated significant cell migration into the hybrids, proliferation, and differentiation into osteoblastic lineage. It was shown that pre-osteoblastic cells are able to mature along the osteoblastic lineage by day 14, when a cell density plateau is reached.…”
Section: Reviewmentioning
confidence: 99%
“…In recent investigations [133,134] it was demonstrated that titanium alloy (Ti-6Al-4V) foams with 52.5% porosity can be filled with a nanofibrous matrix fabricated by self-assembling PA for bone repair. In this way, the bioactivity can be tailored by controlling the orientation and density of the bioactive peptide epitopes, this being the major advantage of this approach.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation